THE MECHANISM OF OPERATION OF THE ONLINE PLATFORM IN THE TRADING SYSTEM AND ITS EFFECTIVENESS (IN THE EXAMPLE OF THE FOM.UZ PLATFORM) (World Economics and Finance Bulletin, 2023)
FOM.UZ it is an online trading platform that revolutionized the trading system in Uzbekistan. This article is aimed at analyzing the mechanism of operation FOM.UZ the platform and its effectiveness in the trade market of Uzbekistan. The article is divided into six sections, starting with an introduction and a description of the history and characteristics of the platform. The methods section provides an overview of the data collection and analysis methods used in the study. The results section lists the results of a study that highlights the effectiveness of the platform and its impact on the trading system. The discussion section explores the outcomes of outcomes and explores potential pathways for future research. Finally, the conclusions and Suggestions section summarizes the main results of the study and makes recommendations to further improve the effectiveness of the platform.
Keywords: FOM.UZ; online platform; trading system